Exosomal miR-2276-5p in Plasma Is a Potential Diagnostic and Prognostic Biomarker in Glioma - Sun, Jingxian; Sun, Zhenying; Gareev, Ilgiz; Yan, Tao; Chen, Xin; Ahmad, Aamir; Zhang, Daming; Zhao, Boxian; Beylerli, Ozal; Yang, Guang; Zhao, Shiguang (Frontiers in Cell and Developmental Biology, 2021)
Introduction Exosomal microRNAs (miRNAs) play an essential role in near and distant intercellular communication and are potential diagnostic and prognostic biomarkers for various cancers. This study focused on evaluation of exosomal miR-2276-5p in plasma as a diagnostic and prognostic biomarker for glioma. Methods Plasma exosomes from 124 patients with glioma and 36 non-tumor controls were collected and subjected to quantitative real-time polymerase chain reaction (qRT-PCR) analysis for the exosomal miR-2276-5p expression. Bioinformatic analyses were performed to identify a gene target, and CGGA and TCGA databases were checked for evaluation of prognostic relevance. Results The exosomal miR-2276-5p in glioma patients had a significantly decreased expression, compared with non-glioma patients (p < 0.01). Receiver operating characteristics (ROC) curve analyses were observed to regulate the diagnostic sensitivity and specificity of miR-2276-5p in glioma; the area under the curve (AUC) for miR-2276-5p was 0.8107. The lower expression of exosomal miR-2276-5p in patients with glioma correlated with poorer survival rates. RAB13 was identified as the target of miR-2276-5p which was high in glioma patients, especially those with higher tumor grades and correlated with poor survival. Conclusion The circulating exosomal miR-2276-5p is significantly reduced in the plasma of glioma patients, and thus, it could be a potential biomarker for patients with glioma for diagnostic and/or prognostic purposes.